A Note on α-multipliers of Prime Rings - Kim, Kyung Ho (GANIT: Journal of Bangladesh Mathematical Society, 2018)
In this paper, we investigate the commutativity of prime rings admitting α-multipliers of R satisfying certain identities and some related results have also been discussed. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 93-98